Cyber Intelligence in National Security - Rezki, Dwi, Sri Astarini; Syaroni Rofii, Muhammad (Journal of Strategic and Global Studies, 2021)
Current information has become a very important commodity. Some even say that our society is already in an "information-based society". The ability to access and provide information quickly and accurately is very important for an organization, such as companies, universities, government agencies, and individuals. Once the importance of the value of information causes often the desired information can only be accessed by certain people. The fall of information in the hands of other parties can cause harm to the information owner. Security issues are an important aspect of an information system management. Unfortunately, this security problem often gets less attention from the owners and managers of information systems. Often security issues are second, or even in the last list of things that are considered important. If it disrupts the performance of a system, security is often reduced or eliminated. Intelligence is information that has been processed, which is used as the basis for making national decisions with a very wide range of observations, including national interests and the establishment of national security, namely the existence of the nation, state sovereignty, national integrity, national stability, and government credibility (raison d'etre intelligence). The use of cyber media that is not escorted can destroy the country's security, welfare and economy. If this applies, the country will lose investors and the country's economy will decline. The economic downturn will eradicate the principle of the state and the state will become riots. With almost all living environments relying on information technology, vulnerability to cyber security will provide a major disaster for the country. Both in terms of economy, politics, security, and others. So it is very important to know how the role of cyber media in the context of state security